Successive rotonation of an N‐heterocyclic imine derived carbonyl: Superelectrophilic dication versus masked acylium ion - Loh, Y; Ángeles Fuentes, M; Vasko, P; Aldridge, S (Wiley, 2018)
Carbonyl cations are among the most commonly invoked reactive intermediates in organic synthesis. While Olah pioneered superacids to provide a “stable ion” environment for their study in situ, isolated examples are rare. Here, we disclose successive protonation of an N‐heterocyclic imine (NHI) derived carbonyl compound (IDippN)2CO, 2, to the monocation [(IDippN)(IDippNH) CO]+, [3]+, and the doubly protonated dication [(IDippNH)2CO]2+, [4]2+. [3]+ represents a rare example of an N‐protonated carbonyl cation and [4]2+ the first example of a superelectrophilic carbonyl dication. All three compounds have been characterized by X‐ray crystallography and IR spectroscopy, revealing stepwise strengthening of the C=O bond on protonation. The unique stability of these systems is attributed to the enhanced basicity and steric profile provided by the NHI substituents. In addition, we report the related singly NHI‐stabilized cation [IDippNCO]+, [5]+. Crystallographic and DFT analyses provide insight into the interaction between the carbonyl fragment and the NHI, which reveals that the [CNCO]+ unit (isoelectronic to CCCO) can be described as an acylium cation “masked” as a cumulene.